Implementation of Work Culture in Improving Organizational Performance in the Serang Sub-district of Serang City Banten - Lala, Elvina Novalianti; Jumiati, Ipah Ema; Pahdi, Nazla Dwi Yana; Suhendar, Danish Arfi (Program Studi Ilmu Administrasi Negara FISIP UNPATTI, 2025)
This study aims to explore the implementation of work culture as a managerial instrument to improve organizational performance in Serang District, Serang City, Banten. The research employs a literature review methodology with descriptive-qualitative analysis. Data were obtained from relevant academic literature, government reports, and official documents to provide comprehensive insights into current work culture practices within local government institutions. The findings reveal that work culture encompassing professionalism, discipline, and collaboration plays a crucial role in supporting the effectiveness and efficiency of public service delivery. These core values serve as the foundation for creating a productive work environment that directly impacts service quality. Effective communication between leaders and employees, coupled with well-structured bureaucratic systems supported by standard operating procedures, emerges as key to successful work culture implementation. This organizational framework ensures consistency, accountability, and transparency in administrative processes. However, significant challenges including limited staff capacity and inadequate facilities hinder optimal organizational performance. These constraints affect government institutions' ability to respond effectively to public needs and demands. Therefore, strengthening human resource capacity through continuous training programs and developing robust information technology infrastructure is essential for enhancing public services and building public trust in local government. The study concludes that sustainable organizational performance improvement requires a holistic approach combining cultural transformation, structural reinforcement, and technological advancement. Strategic interventions focusing on employee development, infrastructure modernization, and policy implementation are necessary to overcome existing barriers and establish a more efficient, responsive, and citizen-oriented public service delivery system.